2011
DOI: 10.1177/1473225411406383
|View full text |Cite
|
Sign up to set email alerts
|

Explicating Correlates of Juvenile Offender Detention Length: The Impact of Race, Mental Health Difficulties, Maltreatment, Offense Type, and Court Dispositions

Abstract: Detention and confinement are widely acknowledged juvenile justice system problems which require further research to understand the explanations for these outcomes. Existing juvenile court, mental health, and child welfare histories were used to explicate factors which predict detention length in this random sample of 342 youth from one large, urban Midwestern county in the United States. Data from this sample revealed eight variables which predict detention length. Legitimate predictors of longer detention le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Similar to research on gender differences in juvenile court outcomes, studies on race differences have also focused on various decision-making stages (Bishop, Leiber, & Johnson, 2010;Guevara, Boyd, Taylor, & Brown, 2011;Rodriguez, 2010;Steen, Bond, Bridges, & Kubrin, 2005). Results continue to demonstrate racial bias in court outcomes in that legal and extralegal factors alone are unable to account for race differences in involvement in the juvenile justice system (Bishop, 2005;Mallett, Stoddard-Dare, & Seck, 2011;Pope & Feyerherm, 1993). This finding highlights a process of cumulative disadvantage that minority youth encounter compared to Whites, where racial disparities at earlier stages lead to more harsh outcomes at the back end of the juvenile justice system (Fagan, 2010;Guevara et al, 2006).…”
Section: Prior Literaturementioning
confidence: 90%
“…Similar to research on gender differences in juvenile court outcomes, studies on race differences have also focused on various decision-making stages (Bishop, Leiber, & Johnson, 2010;Guevara, Boyd, Taylor, & Brown, 2011;Rodriguez, 2010;Steen, Bond, Bridges, & Kubrin, 2005). Results continue to demonstrate racial bias in court outcomes in that legal and extralegal factors alone are unable to account for race differences in involvement in the juvenile justice system (Bishop, 2005;Mallett, Stoddard-Dare, & Seck, 2011;Pope & Feyerherm, 1993). This finding highlights a process of cumulative disadvantage that minority youth encounter compared to Whites, where racial disparities at earlier stages lead to more harsh outcomes at the back end of the juvenile justice system (Fagan, 2010;Guevara et al, 2006).…”
Section: Prior Literaturementioning
confidence: 90%
“…Findings from this retrospective research may help evaluators, court personnel, and mental health professionals to further understand possible risk factors for suicidal ideation among this population. Since suicidal ideation and attempts are linked to many deleterious consequences including delinquency recidivism, it is worthwhile to learn about factors associated with suicide attempts so that at‐risk youth can be identified and treated before additional negative consequences occur (Mallett, Stoddard‐Dare, & Seck, 2011; Mulder, Brand, Bullens, & van Marie, 2011).…”
mentioning
confidence: 99%
“…The finding that adjudicated juveniles with special education report slightly higher rates of recidivism is consistent with prior literature. Specifically, while focused on learning disabilities more generally, past studies have reported that juveniles with learning disabilities are more likely to recidivate compared to those without a learning disability (Mallett et al, 2011; Zhang et al, 2011a). There are many reasons why this may be the case.…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between learning disability and juvenile delinquency has been extensively studied and the prevalence of learning disability is significantly higher among adjudicated juveniles than non-justice-involved juveniles (Defoe et al, 2013; Dowse et al, 2014; Evans et al, 2015; Mallett, 2014; Molina et al, 2014). Youth who have a learning disability have been found to come into contact with the juvenile justice system earlier, receive longer probation supervision, and are more likely to recidivate compared to those without a learning disability (Mallett et al, 2011; Zhang et al, 2011a). Among juveniles with learning disabilities, African Americans and males are particularly likely to reoffend compared to others (Zhang et al, 2011b).…”
Section: Literature Reviewmentioning
confidence: 99%